Analysis of Student Needs for English Teaching Materials in Management Department Faculty of Economics and Business University of Mataram - Husmia, Tria Rizki; Amrullah; Arafiq (Program Studi Pendidikan Bahasa Inggris, 2025)
This study aims to investigates the English language needs of Management Study Program students at the Faculty of Economics and Business, University of Mataram, emphasizing the importance of English for Specific Purposes (ESP). As globalization intensifies, proficiency in English tailored to students’ academic and professional fields becomes critical. Employing a qualitative descriptive method, data were collected from 35 third-semester students through questionnaires and interviews, focusing on their learning needs, goals, and preferred content. Analysis revealed that speaking skills are prioritized by students to enhance their future career prospects, while there is a strong demand for English materials directly related to management contexts. The findings highlight that students require materials that are not only easy to understand but also practically applicable to their future workplaces. This study underscores the need for lecturers to develop specialized English teaching materials that align with students' professional goals and specific disciplines. It also recommends that English teaching at the university level move beyond general proficiency to incorporate industry-relevant language skills. Finally, the study suggests future research involve larger sample sizes to further enrich understanding and curriculum development. The integration of ESP principles into English teaching is essential for preparing graduates who are competent, confident, and ready for the demands of their professions.